1998
DOI: 10.3171/jns.1998.88.2.0293
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgery for cavernous malformations

Abstract: The high incidence of radiation-induced complications does not seem to justify the limited protection the treatment may afford in only exceptional cases. A prospective randomized study is needed before the role of radiosurgery in the management of these lesions can be defined. Until such a study has proved differently, a caveat must be raised for the treatment of CM with GKRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
96
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(104 citation statements)
references
References 16 publications
6
96
0
2
Order By: Relevance
“…A similar thrombooblit erative response is described after the irradiation of CMs. 10,12,28 In support of this finding, the rehemorrhage rate can be significantly reduced after a latent period typi cally 2 years after radiosurgery to allow thrombooblitera tion to occur. 3,7,11,14,21,22,29 The problem in radiological as sessment is that CMs are capillary malformations and so are inherently occult angiographically.…”
supporting
confidence: 60%
“…A similar thrombooblit erative response is described after the irradiation of CMs. 10,12,28 In support of this finding, the rehemorrhage rate can be significantly reduced after a latent period typi cally 2 years after radiosurgery to allow thrombooblitera tion to occur. 3,7,11,14,21,22,29 The problem in radiological as sessment is that CMs are capillary malformations and so are inherently occult angiographically.…”
supporting
confidence: 60%
“…11,39,51,52 In most series, however, an equal distribution between the sexes 13,24,26,31,40,43,48,53 has been reported, and this was also the case in ours. Some authors have suggested a higher propensity for bleeding episodes in female patients, 16,48 often during pregnancy.…”
Section: Age and Sex Of The Patientssupporting
confidence: 47%
“…8 Although some authors report a reduction in the rate of hemorrhage in patients whose CMs are treated with radiosurgery, 21,30 others not only failed to confirm such a reduction but also showed a high incidence of complications induced by radiation. 4,26,42 Gewirtz, et al, 17 found no evidence of vascular obliteration in histopathological samples of CMs that were previously treated with radiation (either conventional radiotherapy or stereotactic radiosurgery), after a mean follow-up period of 3.5 years. There is a report of a cerebellar CM treated with radiosurgery in which the lesion showed reduction without hemorrhage after a mean follow-up duration of 34 months.…”
Section: Neurosurg Focus / Volume 21 / July 2006mentioning
confidence: 99%
See 1 more Smart Citation
“…1,5,7 Other respected groups have declared radiosurgery to be of little to no use, a treatment associated with an unexpectedly high rate of radiosurgery-induced complications for patients. 4,6,9 Groups from both camps frequently publish similar results for other radiosurgical indications. Why is there such disagreement over radiosurgery for CMs?…”
mentioning
confidence: 59%